Prime Editing: A New Way for Genome Editing - Marzec, Marek; Brąszewska-Zalewska, Agnieszka; Hensel, Goetz (Trends in cell biology, 2020)
Precise and efficient use of genome editing tools are hampered by the introduction of DNA double-strand breaks, donor DNA templates, or homology-directed repair. A recent study expands the genome editing toolbox with the introduction of prime editing, which overcomes previous challenges and introduces insertions, deletions, and all putative 12 types of base-to-base conversions in human cells.
Keywords: RNA, Guide, CRISPR-Cas Systems; prime editing; targeted mutagenesis; vodící RNA, systémy CRISPR-Cas; DNA; Gene Editing; genome editing; CRISPR-Cas9; Humans; lidé; editace genu; Hybridization, Genetic; hybridizace genetická